New combinations on Paratibraca Campos & Grazia, 1995 (Hemiptera: Pentatomidae), with description of a new species - Grazia, Jocelia; Barão, Kim R.; Barros, Lurdiana D. (Entomological Communications, 2022)
New combinations for Paratibraca amazonica (Gonçalves & Campos, 2016) comb. n., Paratibraca dubia (Campos & Souza, 2016) comb. n. and Paratibraca spinosa (Campos & Grazia, 1998) comb. n. are proposed. Paratibraca rideri Barros, Barão & Grazia sp. nov. from Brazil is described. Additions to the genus description, and photographs of type-specimens are provided.